The Impact of Organizational Development and Artificial Intelligence on Decision-Making - Dr. Abdul Wahab Samad (Journal of Center for Energy Policy and Human Resources Capacity Development, 2025)
This study's goal is to examine how Artificial Intelligence (AI) and organizational characteristics affect decision-making in organizations by using the SMART PLS approach. A quantitative strategy was used, which involved collecting primary and secondary data through questionnaires and documentation. The research included hypothesis testing, which was carried out with the use of SmartPLS software. The results show that AI has a large and positive impact, with a coefficient of 0.269. This demonstrates how AI improves the efficiency of data analysis, automates processes, and provides data-driven insights that help make decisions more quickly and accurately in changing situations. On the other hand, organizational factors had a greater impact, with a coefficient of 0.824. This highlights the significance of aspects like organizational structure, work culture, and managerial engagement in promoting strategic decisions that are in line with the organization's vision. The quality of decision-making and the overall effectiveness of an organization are improved by the combination of artificial intelligence and organizational aspects